Artificial Nanoplatelets Depend on Size for Precisely Inducing Thrombosis in Tumor Vessels. Issue 5 (28th March 2022) - Zong, Xiaoqing; Liu, Lamei; Yang, Haiyuan; Wu, Jinpei; Yuan, Pengfei; Chen, Xinjie; Yang, Caiqi; Li, Xiaodi; Li, Yuchao; Ji, Xin; Shi, Changzheng; Xue, Wei; et al.
Abstract: Due to the heterogeneity of a tumor, the tumor vascular interruption‐based therapy has become an ideal treatment strategy. Herein, artificial nanoplatelets are reported to induce selective thrombosis in tumor vessels, which can achieve rapid and large‐scale necrosis of tumor cells. For one, the nanoplatelets are exploited to specially release thrombin into target regions without affecting the established coagulation factors system. For another, the thrombin elicits vascular infarction to provide tumor‐ablation effects. More importantly, the size‐dependent effect of nanoplatelets (with diameters of 200, 400, and 800 nm) in vivo on blocking the tumor vessels is evaluated. The results show that the nanoplatelets from nanometer to submicron have achieved different biodistribution and therapeutic effects through the vascular transport. Notably, 400 nm scale nanoplatelets can induce thrombosis in tumor vessels and achieve 83% of the tumor elimination rate, thus manifesting the effectiveness of anti‐tumor strategy compared with the other two scales of nanoplatelets (200 and 800 nm). These findings highlight the need of concern about nanoparticle size, providing a promising strategy for the future design of advanced vascular targeting reagents and the clinical translation of tumor vascular interruption‐based therapy. Abstract : Herein, the artificial nanoplatelets are reported to induce selective thrombosis in tumor vessels. Importantly, the size‐dependent effect of nanoplatelets in vivo on blocking the tumor vessels was evaluated. The results demonstrate that the 400 nm scale artificial nanoplatelets can mimic nature platelets to precisely induce embolization in tumor vessels, thus exhibiting remarkable anti‐tumor effect.